RELATIONSHIP EARLY MARRIAGE WITH GROWTH & DEVELOPMENT OF CHILDREN IN THE ETHNIC MADURA DISTRICT LEKOK PASURUAN - Iis Fatmati (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2014)
Introduction. Early marriage is the beginning of the health problems of women, children and the control population. Marriage is too young the age at first marriage under 18 years of age in sub Lekok Pasuruan strongly influenced by cultural factors madura. The purpose of this study was to determine the effect of early marriage on the quality of growth and development of children in the District Lekok Pasuruan. Methods. The method used a retrospective cohort study. The study population was women who married young age (<18 years) and children under five. Samples were taken by using random sampling. Data were collected and analyzed using Chi Square test. Result. The results showed that 85% of teens got married early, the child’s growth by weight / height 52% of normal and 77% normal child development. Based on Chi Square test was an early marriage to the child’s growth and development of children and the obtained value of p = 0.000. Discussion. This could be due to the influence of culture so entrenched and public education are low at only elementary school in general. Keywords: Early marriage, growth, development, child